The effectiveness of a pocket book on postpartum depression on the knowledge of Pkk mothers in Arang Limbung Village, Kubu Raya District - Azmi, Khulul; Purwanti, Desi Asih; Wulandari, Wulandari (Science Midwifery, 2024)
Postpartum depression is defined as non-psychotic depression that occurs after giving birth for up to six weeks or more. Untreated postpartum depression has an impact on the mother's mental and physical health, requiring special attention to the prevention and management of postpartum depression to improve the health of the mother and child. The research method using a quantitative approach was chosen as the method in this research using a One Group Pre-test-post-test design research design which is included in the quasi-experimental research design. The population taken in this study were PKK mothers in Arang Limbung Village by setting exclusion criteria, namely mothers who had never been pregnant or given birth and the number of samples taken in this study used a total sampling of 40 respondents. The research results showed that the mother's level of knowledge about depression before being given the pocket book was less than 38. It can be concluded that there are still many mothers who do not know what postpartum depression means in mothers. After being given the booklet most mothers (65%) improved to a "good" knowledge level, this shows that the booklet and counseling play an important role in increasing mothers' understanding of postpartum depression.